A photo-crosslinkable bis-triarylamine side-chain polymer as a hole-transport material for stable perovskite solar cells. Issue 1 (18th September 2019) - Tremblay, Marie-Hélène; Schutt, Kelly; Zhang, Yadong; Lim, Jongchul; Lin, Yen-Hung; Warby, Jonathan H.; Barlow, Stephen; Snaith, Henry J.; Marder, Seth R.
Abstract : A crosslinkable acrylate random copolymer with both bis(triarylamine) and photocrosslinkable cinnamate side chains is compared to the widely used poly(4-butyl-triphenylamine-4′, 4′′-diyl) as a hole-transport material in perovskite solar cells. Abstract : A crosslinkable acrylate random copolymer with both hole-transporting bis(triarylamine) and photocrosslinkable cinnamate side chains is compared to the widely used poly(4-butyl-triphenylamine-4′, 4′′-diyl) (PolyTPD) as a hole-transport material (HTM) in positive–intrinsic–negative (p–i–n) perovskite solar cells (PSCs). The crosslinked films of this HTM exhibit improved wettability by precursor solutions of the perovskite relative to PolyTPD; this facilitates high-quality full film coverage by the subsequently deposited perovskite layer on smooth substrates, which is difficult to achieve with PolyTPD without the use of additional interlayers. PSCs fabricated using undoped and crosslinked copolymer achieve steady-state power outputs that are comparable to those of cells incorporating p-doped PolyTPD (with interlayers) as the HTM. The devices made with this material also exhibited improved initial stability under high-intensity ultraviolet LED irradiation, in comparison to those with the PolyTPD analogue. Remarkably, after 3000 h of aging in an oven at 85 °C in a nitrogen-filled glovebox, device efficiency showed no degradation; the SPO was comparable to the initial performance.